Residual punching shear capacity of corroded reinforced concrete slabs - Yang, Zhihong (2022)
Steel reinforcement corrosion is becoming a critical issue since more old buildings are still in operations with great probability of substantial corrosion in reinforcements. The strength and serviceability of corroded RC slab is remarkably impacted by the corrosion. Therefore, it is vital to understand more about the punching shear mechanism of the slabs subjected to corrosion effects in order to make a good prediction on its residual capacity. In this paper, critical shear crack theory (CSCT) was further developed to predict the residual punching shear strength of corroded RC slabs, considering the material properties deterioration induced by the corrosion. The effectiveness of modified CSCT was verified by comparing with the available experimental results. In addition, a validated FEM model that considers the material deterioration and bond degradation was proposed to verify the accuracy of proposed model. Finally, a parametric study, including 240 cases, was conducted to investigate the effect of some important factors on punching shear behavior of corroded RC slabs based on modified CSCT. The outcomes demonstrated that the residual punching shear capacity predicted by the proposed model is more accurate than existing design codes. The predicted failure modes had also shown fairly good agreement with the experimental results.